An Examination of Palliative or End-of-Life Care Education in Introductory Nursing Programs across Canada - Donna M. Wilson; Barbara L. Goodwin; Jessica A. Hewitt (Hindawi Limited, 2011)
An investigation was done to assess for and describe the end-of-life education provided in Canadian nursing programs to prepare students for practice. All 35 university nursing schools/faculties were surveyed in 2004; 29 (82.9%) responded. At that time, all but one routinely provided this education, with that school developing a course (implemented the next year). As compared to past surveys, this survey revealed more class time, practicum hours, and topics covered, with this content and experiences deliberately planned and placed in curriculums. A check in 2010 revealed that all of these schools were providing death education similar to that described in 2004. These findings indicate that nurse educators recognize the need for all nurses to be prepared to care for dying persons and their families. Regardless, more needs to be done to ensure novice nurses feel capable of providing end-of-life care. Death education developments will be needed as deaths increase with population aging.